2015
DOI: 10.1016/j.socscimed.2015.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of neighborhood socioeconomic characteristics and alcohol availability on drinking: Results from the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Neighborhood socioeconomic characteristics and alcohol availability may affect alcohol consumption, but adequate longitudinal research to support these hypotheses does not exist. We used data from the Multi-Ethnic Study of Atherosclerosis (MESA) (N= 6163) to examine associations of changes in neighborhood socioeconomic status (SES) and alcohol outlet density, with current, weekly, and heavy daily alcohol consumption in hybrid effects models. We also examined whether these associations were moderated by gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 66 publications
(82 reference statements)
2
24
0
2
Order By: Relevance
“…Five factors, capturing 74% of the variance, explained were retained. [50] The scales are linked to MESA participants by census tract using Census 2000 data for years 2000–2004, ACS 2005- 2009 data for years 2005–2007, and ACS 2007-2011 data for years 2008–2012.…”
Section: The Characterization Of Neighborhood Environments In Mesamentioning
confidence: 99%
See 1 more Smart Citation
“…Five factors, capturing 74% of the variance, explained were retained. [50] The scales are linked to MESA participants by census tract using Census 2000 data for years 2000–2004, ACS 2005- 2009 data for years 2005–2007, and ACS 2007-2011 data for years 2008–2012.…”
Section: The Characterization Of Neighborhood Environments In Mesamentioning
confidence: 99%
“…[50] Increases in liquor store densities[50] and neighborhood foreclosures were associated with increases in weekly alcohol consumption. Increases in neighborhood-level foreclosure were associated with decreases in the number of cigarettes smoked (Crawford N et al, unpublished).…”
Section: Select Findings To Datementioning
confidence: 99%
“…For a sample of Finnish adults (mean age=44.2 years), decreasing the distance to the nearest on-premise venue was associated with increases in heavy alcohol use (Halonen et al, 2013). In contrast, two studies have examined the relationship between off-premise licences (e.g., liquor stores) and alcohol consumption, and both identified significant effects (Brenner et al, 2015, Cooper et al, 2013. Brenner et al (2016) found that increasing off-premise licence density within 1 mile from home was associated with increased alcohol consumption among older adults (mean baseline age=61.9 years), and Cooper et al (2013) found that a reduction in outlet density/square mile equated to reduced odds of binge drinking among public housing tenants who relocated (mean baseline age=43.1 years).…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable cross-sectional evidence, few longitudinal studies have tested whether there is a relationship between alcohol outlet density and adults' individual-level alcohol consumption (Bryden et al, 2012, Gmel et al, 2015. Three studies have examined associations between the density of, or proximity to, on-premise venues (e.g., bars, nightclubs, taverns) (Picone et al, 2010, Brenner et al, 2015, Halonen et al, 2013, but just one identified a significant relationship. For a sample of Finnish adults (mean age=44.2 years), decreasing the distance to the nearest on-premise venue was associated with increases in heavy alcohol use (Halonen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation